Structural and stability differences among GI norovirus virus-like particles produced in silkworm–baculovirus expression vector system - Tsurumi, Yuto; Masuda, Akitsu; Xu, Jian; Mon, Hiroaki; Kusakabe, Takahiro; Lee, Jae Man (Frontiers in Microbiology, 2026)
Norovirus (NoV) is a leading cause of acute gastroenteritis worldwide, with genogroups I and II (GI and GII) most frequently detected. NoV Virus-like particles (VLPs) composed of the major capsid protein VP1 (~60 kDa) are essential for vaccine development, yet GI VLPs remain poorly characterized. In this study, VP1 from four epidemiologically relevant GI genotypes was expressed using the silkworm-baculovirus system, and purification conditions were optimized in a genotype-specific manner. Purified VLPs were analyzed using size-exclusion chromatography (SEC), dynamic light scattering (DLS), transmission electron microscopy (TEM), and differential scanning fluorimetry (DSF), and their functional epitopes confirmed via binding to histo-blood group antigens (HBGAs) mimics. Stability assessments revealed genotype-dependent differences in pH and thermal tolerance, including aggregation and structural transitions. Collectively, these findings define genotype-specific purification, structural characterization, and stability profiles for four GI NoV VLPs. This work provides the first systematic framework for understanding GI-specific constraints in VLP production and offers foundational data that directly inform the design and formulation of multivalent NoV vaccines.